Alejandría, una ciudad neoliberal: ultraconcentración, invasión pausada, división social simbólica y franquicias - Vizcaíno Pina, María José; Vizcaíno Pina, Pedro Antonio (El Colegio de México A.C., 2018)
The current map of the Egyptian Alexandria enables us to explain the neoliberal urban planning process. In the city occurs an intensive process of creative destruction in an environment that suffers the consequent problems of rising ultra-concentration, aggravated by a lack of a coherent state planning. Urban development without planning is visible in the “quiet encroachment” process that citizens develop in the streets and in the decadent condition of the public space. According to our research, Alexandrian urban planning development is made under a symbolic social division that opposes the cultural city to the elite consumerist city. Fast-food franchises are distinctive symbols of urban neoliberalism.